Relasi Kelisanan Al-Qur’an dan Pancasila Dalam Upaya Menjaga dan Mengembangkan Identitas Islam Indonesia - Alwi HS, Muhammad; Hamid, Nur (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2019)
Yudian Wahyudi voiced his idea that Indonesia (read: Pancasila) is a religious and secular country simultaneously. The idea arose because many said Indonesia was a secular country, on the other hand, it was also mentioned that Indonesia was a religious country. It is said as a secular country because Indonesia has a lot of 'oriented' to the West. While referred to as a religious country because it has the majority Muslim population in the world. This paper will explain the position of the Pancasila as the way of life of the Indonesian people, associated with the Qur'an which is a way of life for Muslims. In this context, al-Qur'an will be explained as the realm of its orality, as is the identity of the Qur'an delivered verbally: from Allah, the Angel Gabriel, the Prophet Muhammad to the Arab community (audience). In this case, reading the oral side of the Koran, through the theory of Orality from Walter J. Ong, will be important if it is realized that there are distinct characteristics for oral delivery, one of which is the context that was born in the oral demands of the present, that is, when the Qur'an is delivered verbally, then the solution-problem or message delivered is based on the current context. At this point, Pancasila is present on Indonesian soil to answer problems and give messages that are also based on the Indonesian context. Also, through the integration of general knowledge in understanding and applying the values of Pancasila and the beauty of the Qur'an, it will give birth to a national and religious attitude that always responds to the development of the times appropriately. Both of these life guidelines maintain Indonesia's existing identity - which is good and advance the life of the nation and state.Â